Vaginal Deliveries and Frequency of Perineal Tears (Medical Forum Monthly, 2024)
Objective: To determine the frequency, risk factors, and severity of perineal tears in women during vaginal delivery.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Nishtar hospital, Multan in the labour room from January 2023 to October 2023.Methods: The study commenced after receiving approval from the ethical committee to collect patient information. The study included 200 patients aged 20 to 40 years, both primipara and multipara. A complete history of patients was taken and the weight of babies at the time of birth was recorded. By following standard protocol detailed examination of the cervix, vagina, vulva, and perineum was done during 3rd stage of labor to diagnose any injury or tear.Results: The mean age of the 200 study patients was 32.64 ± 6.89 years, and the mean BMI was 23.25 ± 2.02 kg/m². Most patients, specifically 94 (47.0%), had a parity of 1, while 21 patients (10.5%) had a parity of 4 or more. Additionally, 113 babies (56.5%) had a birth weight of ≤3 kg, whereas 87 babies (43.5%) had a birth weight of over 3 kg. Perineal tears were observed in 169 patients (84.5%), with the majority experiencing first-degree perineal tears.Conclusion: The study highlights that perineal trauma during vaginal delivery is highly prevalent, with our research identifying a frequency of 84.5% for perineal tears. Among these, first-degree perineal tears were the most common. Perineal tears contribute significantly to maternal morbidity.